Comparison of Different Phenotypic Tests versus PCR in the Detection of Carbapenemase-Producing Pseudomonas aeruginosa Isolates in Hamadan, Iran - Masoumeh Beig; Mohammad Taheri; Mohammad Reza Arabestani (International Journal of Microbiology)
In recent years, the prevalence of carbapenem-resistant Pseudomonas aeruginosa isolates has become a worldwide concern. Rapid and accurate detection of carbapenemase-producing P. aeruginosa isolates is so important. The aim of this study was to evaluate the performance of the phenotypic methods such as Modified Hodge test (MHT), CarbaNP (CNPt), combined double-disk synergy test (CDDT), and carbapenem inactivation method (CIM) for rapid and accurate detection of clinical carbapenemase production of P. aeruginosa isolates. This study was performed on 97 P. aeruginosa strains, which were isolated from clinical samples in Hamadan hospitals, western Iran in 2017-2018. Antibiotic susceptibility testing was performed using disk diffusion and minimum inhibitory concentration (MIC) by E-test method. We evaluated the performance of MHT, CarbaNP, CDDT, and CIM tests in comparison to polymerase chain reaction (PCR) for the detection of carbapenemase-producing isolates. Additionally, the presence of carbapenem-resistant genes was investigated using the PCR method. Our findings showed that the highest resistance was to cefoxitin (94.8%). Moreover, among the carbapenem antibiotics, the highest resistance was to imipenem (49.4%). Among the 49 carbapenem-resistant isolates, 42 (85.7%) isolates were MIC positive. The results of phenotypic tests showed that CarbaNP, CIM, CDDT, and MHT tests were positive in (48/49, 97.95%), (46/49, 93.87%), (27/49, 57.44%), and (25/49, 53.19%) of isolates, respectively. CarbaNP and CIM tests showed high sensitivity, specificity, positive predictive values (PPV), and negative predictive values (NPV) compared to PCR in P. aeruginosa isolates. CarbaNP and CIM tests are highly sensitive and specific tests for identifying carbapenemase-producing P. aeruginosa isolates.